Hot stamping materials
A hot stamping material with controlled alloying elements and fine precipitates effectively traps hydrogen, addressing hydrogen delayed fracture issues in high-strength steel, achieving superior mechanical properties and reduced failure risks.
Patent Information
- Application Number
- JP2024534626
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-10
- Filing Date
- 2022-12-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
High-strength steel used in automotive parts faces issues with hydrogen delayed fracture due to hydrogen inflow during the hot-stamping process, leading to reduced mechanical properties and increased risk of material failure.
A hot stamping material comprising specific alloying elements and fine precipitates, such as titanium, niobium, and vanadium nitrides or carbides, is developed to trap hydrogen, ensuring high strength, durability, and improved hydrogen delayed fracture characteristics.
The material achieves tensile strengths of 1,680 MPa or more, bending angles of 40° or more, and activated hydrogen amounts of 0.5 wppm or less, enhancing the mechanical properties and reducing hydrogen-induced failures in hot-stamped parts.
Smart Images

Figure 2024546126000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a material for hot stamping, and more particularly to a material for hot stamping that can ensure excellent mechanical properties and hydrogen delayed fracture properties of hot stamped parts. [Background technology]
[0002] High-strength steel is used for parts used in automobiles, etc., for the purpose of weight reduction and stability. Although the high-strength steel can ensure high strength characteristics relative to weight, the increased strength reduces press formability, and the material may break during processing or a springback phenomenon may occur, making it difficult to form products with complex and precise shapes.
[0003] As a representative method for solving such problems, there is a hot stamping method, and as interest in the hot stamping method has increased, research into materials for hot stamping has also been actively conducted. For example, as disclosed in Korean Patent Publication No. 10-2017-0076009, the hot stamping method is a forming technology for manufacturing high-strength parts by heating a boron steel sheet to an appropriate temperature, forming it in a press die, and then rapidly cooling it. According to the invention of Korean Patent Publication No. 10-2017-0076009, problems such as crack generation during forming or poor shape freezing, which are problems with high-strength steel sheets, are suppressed, and parts with good precision can be manufactured.
[0004] However, in the case of hot stamping steel sheets, there is a problem that hydrogen delayed fracture occurs due to hydrogen and residual stress introduced during the hot stamping process. In relation to this, Korean Patent Publication No. 10-2020-0061922 discloses that a hot stamping blank is preheated before being heated to a high temperature to form a thin oxide layer on the surface of the blank, thereby blocking hydrogen inflow during the high-temperature heating process and minimizing hydrogen delayed fracture. However, since it is impossible to completely block hydrogen inflow, there is a concern that hydrogen delayed fracture may occur because the introduced hydrogen cannot be controlled. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention is directed to solving various problems including those mentioned above, and provides a hot stamping material that can ensure high strength, excellent mechanical properties such as high resistance, and improved hydrogen delayed fracture properties of hot stamping parts, and a manufacturing method thereof. However, such problems are merely examples, and the scope of the present invention is not limited thereby. [Means for solving the problem]
[0006] A hot stamping material according to an embodiment of the present invention is a steel sheet containing 0.28 to 0.50 weight percent carbon (C), 0.15 to 0.70 weight percent silicon (Si), 0.5 to 2.0 weight percent manganese (Mn), 0.05 weight percent or less phosphorus (P), 0.01 weight percent or less sulfur (S), 0.1 to 0.5 weight percent chromium (Cr), 0.001 to 0.005 weight percent boron (B), 0.1 weight percent or less additives, and the balance iron (Fe) and other unavoidable impurities. and fine precipitates distributed within the steel sheet; the additive includes at least one of titanium (Ti), niobium (Nb) and vanadium (V), the fine precipitates include at least one nitride or carbide of titanium (Ti), niobium (Nb) and vanadium (V), trap hydrogen, and a diameter average variation coefficient, which is a value obtained by dividing the standard deviation of the diameter average of the fine precipitates by the diameter average of the fine precipitates, is 0.7 or less.
[0007] The hot stamping material may exhibit a tensile strength of 1,680 MPa or more, a bending angle of 40° or more, and an activated hydrogen content of 0.5 wppm or less after hot stamping.
[0008] The fine precipitates also have an average diameter of 0.006 μm or less.
[0009] At least 90% of the fine precipitates may have a diameter of 0.01 μm or less.
[0010] At least 60% of the fine precipitates may have a diameter of 0.005 μm or less.
[0011] The unit area (100 μm 2 ) is equal to or greater than 25,000 and equal to or less than 30,000.
[0012] The unit area (100 μm) of fine precipitates with a diameter of 0.01 μm or less 2 ) is equal to or greater than 23,000 and equal to or less than 29,000.
[0013] The unit area (100 μm) of fine precipitates with a diameter of 0.005 μm or less 2 ) is equal to or greater than 15,200 and equal to or less than 29,000.
[0014] The coefficient of variation in number, which is the value obtained by dividing the standard deviation of the number average of the fine precipitates by the number average of the fine precipitates, is also 0.8 or less.
[0015] A material for hot stamping according to an embodiment of the present invention is a steel plate containing carbon (C): 0.28-0.50 wt%, silicon (Si): 0.15-0.70 wt%, manganese (Mn): 0.5-2.0 wt%, phosphorus (P): 0.05 wt% or less, sulfur (S): 0.01 wt% or less, chromium (Cr): 0.1-0.5 wt%, boron (B): 0.001-0.005 wt%, additives: 0.1 wt% or less, the balance being iron (Fe) and other unavoidable impurities; and fine precipitates distributed within the steel plate; the additive includes at least one of titanium (Ti), niobium (Nb) and vanadium (V), the fine precipitates include at least one nitride or carbide of titanium (Ti), niobium (Nb) and vanadium (V), trap hydrogen, and a number variation coefficient, which is a value obtained by dividing the standard deviation of the number average of the fine precipitates by the number average of the fine precipitates, is 0.8 or less.
[0016] The hot stamping material may exhibit a tensile strength of 1,680 MPa or more, a bending angle of 40° or more, and an activated hydrogen content of 0.5 wppm or less after hot stamping.
[0017] A first number variation coefficient, which is a value obtained by dividing the standard deviation of the number average of fine precipitates having a diameter of 0.01 μm or less among the fine precipitates, by the number average of the fine precipitates having a diameter of 0.01 μm or less, is also 0.8 or less.
[0018] A second number variation coefficient, which is the standard deviation of the number average of fine precipitates having a diameter of 0.005 μm or less among the fine precipitates, divided by the number average of the fine precipitates having a diameter of 0.005 μm or less, is also 0.8 or less.
[0019] The unit area (100 μm 2 ) is equal to or greater than 25,000 and equal to or less than 30,000.
[0020] The unit area (100 μm) of fine precipitates with a diameter of 0.01 μm or less 2 ) is equal to or greater than 23,000 and equal to or less than 29,000.
[0021] The unit area (100 μm) of fine precipitates with a diameter of 0.005 μm or less 2 ) is equal to or greater than 15,200 and equal to or less than 29,000.
[0022] The fine precipitates also have an average diameter of 0.006 μm or less.
[0023] At least 90% of the fine precipitates may have a diameter of 0.01 μm or less.
[0024] At least 60% of the fine precipitates may have a diameter of 0.005 μm or less. Effect of the Invention
[0025] According to the embodiments of the present invention, a hot stamping material that can ensure high strength, excellent mechanical properties, high resistance, and improved hydrogen delayed fracture properties of a hot stamping part, and a manufacturing method thereof can be realized, but the scope of the present invention is not limited by such effects. [Brief description of the drawings]
[0026] [Figure 1]1 is a transmission electron microscope (TEM) image illustrating a portion of a hot stamping material according to an embodiment of the present invention. [Figure 2A] FIG. 2 is a diagram illustrating a schematic view of a portion of fine precipitates dispersed according to one embodiment of the present invention. [Figure 2B] FIG. 2 is a diagram illustrating a schematic view of a portion of fine precipitates dispersed according to one embodiment of the present invention. [Figure 3A] FIG. 2 is an exemplary diagram illustrating a part of a state in which hydrogen is trapped in fine precipitates. [Figure 3B] FIG. 2 is an exemplary diagram illustrating a part of a state in which hydrogen is trapped in fine precipitates. [Figure 4] 1 is a flow chart that generally illustrates a method for manufacturing a blank for hot stamping, according to one embodiment of the present invention. [Diagram 5] 1 is a graph showing a comparison of tensile strength and bending stress depending on winding temperature in an embodiment of the present invention and a comparative example. [Figure 6A] 1 is an image illustrating the results of a 4-point bending test according to the winding temperature of the embodiment. [Figure 6B] 1 is an image illustrating the results of a 4-point bending test according to the winding temperature of a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention can be modified in various ways and can have various embodiments, but specific embodiments are illustrated in the drawings and will be described in detail by the detailed description. The advantages, features, and methods of achieving the present invention will become clear by referring to the embodiments described in detail below together with the drawings. However, the present invention is not limited to the embodiments disclosed below, but can be embodied in various forms.
[0028] Hereinafter, an embodiment of the present invention will be described in detail with reference to the accompanying drawings. When describing the embodiment with reference to the drawings, the same or corresponding components are designated by the same reference numerals, and duplicate descriptions thereof will be omitted.
[0029] In the following examples, terms such as "first" and "second" are not used in a limiting sense but are used only to distinguish one component from another component.
[0030] In the following examples, the singular expression includes the plural expression unless the context clearly indicates otherwise.
[0031] In the following examples, terms such as "comprise" or "have" mean the presence of features or components described in the specification, without precluding the possibility that one or more other features or components may also be added.
[0032] In the following examples, when a part such as a film, region, or component is said to be "on" or "above" another part, this does not only mean that it is directly on top of the other part, but also includes cases where there are other films, regions, components, etc. interposed between them.
[0033] In the drawings, the size of components may be exaggerated or reduced for the convenience of explanation. For example, the size and thickness of each component shown in the drawings are arbitrarily shown for the convenience of explanation, and the present invention is not necessarily limited to what is shown in the drawings.
[0034] If an embodiment can be implemented differently, the order of certain steps may be performed differently than that described, for example, two steps described as successive may be performed substantially simultaneously or may be performed in the reverse order from that described.
[0035] In this specification, "A and / or B" refers to the case where A is A, B is B, or A and B is B. And, "at least one of A and B" refers to the case where A is A, B is B, or A and B is B.
[0036] In the following examples, when a membrane, region, component, etc. is said to be connected, this includes cases where the membrane, region, component, etc. are directly connected, and / or cases where the membrane, region, component, etc. are indirectly connected with another membrane, region, component, etc. being interposed between them. For example, in this specification, when a membrane, region, component, etc. is said to be electrically connected, this includes cases where the membrane, region, component, etc. are directly electrically connected, and / or cases where the membrane, region, component, etc. are indirectly electrically connected with another membrane, region, component, etc. being interposed between them.
[0037] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0038] FIG. 1 is a transmission electron microscope (TEM) image illustrating a portion of a hot stamping blank according to one embodiment of the present invention.
[0039] As shown in FIG. 1, a blank 1 for hot stamping according to an embodiment of the present invention includes a steel sheet 10 and fine precipitates 20 distributed within the steel sheet 10 .
[0040] The hot stamping blank 1 can be controlled so that the content of alloy elements contained in the steel sheet 10 and the precipitation behavior of the fine precipitates 20 satisfy preset conditions. Through this, the formed part after hot stamping can have excellent mechanical properties such as high strength and high resistance, and improved hydrogen delayed fracture properties. In one embodiment, the hot stamping blank 1 can exhibit a tensile strength of 1,680 MPa or more, preferably 1,680 MPa or more and less than 2,300 MPa, after hot stamping. In addition, it can exhibit a bending angle of 40° or more and an activated hydrogen content of 0.5 wppm or less. Here, the "bending angle" can mean a V-bending angle in the rolling direction (RD).
[0041] The steel sheet 10 is also a steel sheet manufactured by performing a hot rolling process and / or a cold rolling process on a slab that is cast so as to contain a predetermined content of a predetermined alloy element. The steel sheet 10 also contains carbon (C), silicon (Si), manganese (Mn), phosphorus (P), sulfur (S), chromium (Cr), boron (B), and the balance iron (Fe), as well as other unavoidable impurities. In one embodiment, the steel sheet 10 also further contains at least one of titanium (Ti), niobium (Nb), and vanadium (V) as an additive. Alternatively, the steel sheet 10 also further contains a predetermined content of calcium (Ca).
[0042] In one embodiment, the steel plate 10 contains carbon (C): 0.28 to 0.50 weight%, silicon (Si): 0.15 to 0.70 weight%, manganese (Mn): 0.5 to 2.0 weight%, phosphorus (P): more than 0 to 0.05 weight%, sulfur (S): more than 0 to 0.01 weight%, chromium (Cr): 0.1 to 0.5 weight%, boron (B): 0.001 to 0.005 weight%, and as additives, the sum of one or more of titanium (Ti), niobium (Nb), and vanadium (V): more than 0 to 0.1 wt%, and the balance iron (Fe) and other unavoidable impurities.
[0043] Carbon (C) acts as an austenite stabilizing element in the steel sheet 10. Carbon is a major element that determines the strength and hardness of the steel sheet 10, and may be added for the purpose of ensuring the tensile strength (e.g., tensile strength of 1,680 MPa or more) and hardenability characteristics of the steel sheet 10 after the hot stamping process. Such carbon is contained in an amount of about 0.28 wt% to about 0.50 wt% based on the total weight of the steel sheet 10. If the carbon content is less than about 0.28 wt%, it is difficult to ensure a hard phase (such as martensite), and it is difficult to satisfy the mechanical strength of the steel sheet 10. On the other hand, if the carbon content exceeds about 0.50 wt%, problems such as brittleness of the steel sheet 10 or reduced bending performance may occur.
[0044] Silicon (Si) can act as a ferrite stabilizing element in the steel sheet 10. Silicon (Si) is a solid solution strengthening element, and can improve the ductility of the steel sheet 10 and can improve the carbon concentration in the austenite by suppressing the formation of low temperature region carbides. Silicon is also a key element for homogenizing the hot rolling, cold rolling, and hot pressing structure (controlling pearlite and manganese segregation zones) and finely dispersing ferrite. Silicon acts as an element for controlling martensite strength heterogeneity and plays a role in improving crash performance. Such silicon is contained in an amount of about 0.15 wt% to about 0.70 wt% based on the total weight of the steel sheet 10. If the silicon content is less than 0.15 wt%, it is difficult to obtain the above-mentioned effects, and cementite may be formed and coarsened in the final hot stamping martensite structure, but the homogenizing effect of the steel sheet 10 is insignificant, and it may not be possible to ensure a V-bending angle. On the other hand, if the silicon content exceeds about 0.70 wt%, the hot rolling load and cold rolling load increase, and hot rolling red scale becomes excessive, which may deteriorate the plating properties of the steel sheet 10.
[0045] Manganese (Mn) acts as an austenite stabilizing element in the steel sheet 10. Manganese may be added to increase hardenability and strength during heat treatment. Such manganese is included in an amount of about 0.5 wt% to about 2.0 wt% based on the total weight of the steel sheet 10. If the manganese content is less than about 0.5 wt%, the grain refining effect is insufficient, and hardenability is insufficient, resulting in insufficient hard phase fraction in the formed product after hot stamping. In addition, if the manganese content exceeds about 2.0 wt%, manganese segregation or pearlite bands may reduce ductility and resistance, causing a decrease in bending performance, and a non-uniform microstructure may occur.
[0046] Phosphorus (P) is contained in an amount of more than 0 and not more than about 0.05 wt% based on the total weight of the steel sheet 10 in order to prevent a decrease in the durability of the steel sheet 10. If the phosphorus content exceeds about 0.05 wt%, iron phosphide compounds are formed, which decreases durability and weldability and may induce cracks in the steel sheet 10 during the manufacturing process.
[0047] Sulfur (S) is contained in an amount of more than 0 and not more than about 0.01 wt% based on the total weight of the steel plate 10. If the sulfur content exceeds about 0.01 wt%, hot workability, weldability, and impact properties are reduced, and surface defects such as cracks may occur due to the formation of large inclusions.
[0048] Chromium (Cr) may be added to improve the hardenability and strength of the steel sheet 10. Chromium may enable grain refinement and strength assurance through precipitation hardening. Such chromium is included in an amount of about 0.1 wt% to about 0.5 wt% based on the total weight of the steel sheet 10. If the chromium content is less than about 0.1 wt%, the precipitation hardening effect is poor, whereas if the chromium content exceeds 0.5 wt%, the amount of Cr-based precipitates and matrix solid solution increases, reducing durability and increasing production costs due to increased costs.
[0049] Boron (B) can be added to suppress ferrite transformation, pearlite transformation, and bainite transformation and ensure the martensite structure, thereby ensuring the hardenability and strength of the steel sheet 10. Boron can also have a grain refinement effect by segregating to grain boundaries to lower grain boundary energy and increase hardenability, and by increasing the austenite grain growth temperature. Such boron is contained in an amount of about 0.001 wt% to about 0.005 wt% based on the total weight of the steel sheet 10. When boron is contained in the above range, it is possible to prevent the occurrence of hard phase grain boundary embrittlement and ensure high resistance and bendability. If the boron content is less than about 0.001 wt%, the hardenability effect is insufficient. Conversely, if the boron content is more than about 0.005 wt%, the solid solubility is low and boron is easily precipitated at grain boundaries depending on the heat treatment conditions, which may deteriorate the hardenability or cause high-temperature embrittlement, and the durability and bendability may be reduced due to the occurrence of hard phase grain boundary embrittlement.
[0050] The additives are elements that produce nitrides or carbides that contribute to the formation of fine precipitates 20. Specifically, the additives include at least one of titanium (Ti), niobium (Nb), and vanadium (V). Titanium (Ti), niobium (Nb), and vanadium (V) can ensure the strength of a hot stamped and quenched member by forming fine precipitates 20 in the form of nitrides or carbides. In addition, they are contained in Fe-Mn-based composite oxides and function as hydrogen trapping sites that are effective in improving delayed fracture resistance, and are also elements necessary for improving delayed fracture resistance. Such additives are contained in a total amount of more than 0 and not more than about 0.1 wt% based on the total weight of the steel plate 10. If the content of the additives exceeds about 0.1 wt%, the increase in yield strength may be excessively large.
[0051] Titanium (Ti) can be added for the purpose of strengthening hardenability and improving material properties by forming precipitates after hot press heat treatment. In addition, at high temperatures, it forms a precipitate phase such as Ti(C,N) and effectively contributes to refinement of austenite grains. Such titanium is contained in an amount of about 0.01 wt% to about 0.05 wt% based on the total weight of the steel sheet 10. If titanium is contained in the above content range, continuous casting defects and coarsening of precipitates can be prevented, the physical properties of the steel material can be easily secured, and defects such as cracks on the steel material surface can be prevented. In addition, if the titanium content exceeds about 0.05 wt%, the precipitates can be coarsened, resulting in a decrease in elongation and bendability.
[0052] Niobium (Nb) and vanadium (V) may be added to increase strength and durability by reducing martensite packet size. Niobium and vanadium are each included in the steel sheet 10 in an amount of about 0.01 wt% to about 0.05 wt% based on the total weight of the steel sheet 10. When niobium and vanadium are included in the above ranges, they have an excellent effect of refining the crystal grains of the steel material in the hot rolling process and the cold rolling process, and can prevent cracks in the slab and brittle fracture of the product during steelmaking / continuous casting, and can minimize the generation of coarse precipitates in steelmaking.
[0053] In addition, when the additives include titanium (Ti) and niobium (Nb), the titanium (Ti) and niobium (Nb) may be contained in a total amount of about 0.02 wt% to about 0.09 wt% based on the total weight of the steel plate 10, but are not limited thereto.
[0054] Calcium (Ca) may be added to control the shape of inclusions. Such calcium is present in an amount of about 0.003 wt% or less based on the total weight of the steel sheet 10.
[0055] The fine precipitates 20 are distributed in the steel sheet 10 and can trap hydrogen. That is, the fine precipitates 20 can improve hydrogen delayed fracture properties of a hot stamped product by providing trapping sites for hydrogen that flows into the hot stamping material 1 during or after its manufacture. In one embodiment, the fine precipitates 20 can include nitrides or carbides of additives. Specifically, the fine precipitates 20 can include nitrides or carbides of at least one of titanium (Ti), niobium (Nb), and vanadium (V).
[0056] The precipitation behavior of the fine precipitates 20 can be controlled by adjusting process conditions. For example, by adjusting the coiling temperature (CT) range among the process conditions, precipitation behavior such as the number of fine precipitates 20, the average distance between the fine precipitates 20, and the diameter of the fine precipitates 20 can be controlled. The process conditions will be described later with reference to FIG. 4. The precipitation behavior of the fine precipitates 20 can be controlled to satisfy preset conditions. In addition, the precipitation behavior of such fine precipitates 20 can be controlled via process conditions (e.g., coiling temperature (CT range). For example, the number of fine precipitates 20 per unit area, the number variation coefficient (C1) indicating the uniformity of the number distribution per unit area, the average distance between fine precipitates 20, the diameter of the fine precipitates 20, the average diameter variation coefficient (C2, C21, C22) indicating the uniformity of the diameter distribution per unit area, etc. can be controlled to satisfy preset conditions. The process conditions will be described later with reference to FIGS. 4 and 5. The precipitation behavior conditions related to the number variation coefficient (C1) and the average diameter variation coefficient (C2, C21, C22) will be described in more detail later through examples and comparative examples.
[0057] The precipitation behavior of the fine precipitates 20 can be measured by analyzing a transmission electron microscope (TEM) image. Specifically, a preset number of TEM images of arbitrary regions of a specimen are acquired. From the acquired images, the fine precipitates 20 are extracted through an image analysis program, and the number of the fine precipitates 20, the average distance between the fine precipitates 20, the diameter of the fine precipitates 20, etc. can be measured for the extracted fine precipitates 20.
[0058] In one embodiment, a surface replication method may be applied as a pretreatment for a test specimen to measure the precipitation behavior of the fine precipitates 20. For example, a one-step replica method, a two-step replica method, an extraction replica method, etc. may be applied, but are not limited to the above examples.
[0059] Alternatively, when measuring the diameter of the fine precipitates 20, the shape of the fine precipitates 20 may be converted into a circle in consideration of the non-uniformity of the morphology of the fine precipitates 20, and the diameter of the fine precipitates 20 may be calculated. Specifically, the area of the fine precipitates 20 extracted using a unit pixel having a specific area may be measured, and the fine precipitates 20 may be converted into a circle having the same area as the measured area, and the diameter of the fine precipitates 20 may be calculated.
[0060] Alternatively, the average distance between the fine precipitates 20 may be measured via a mean free path. Specifically, the average distance between the fine precipitates 20 may be calculated using the particle area fraction and the number of particles per unit length. For example, the average distance between the fine precipitates 20 may have a correlation as shown in Equation 1 below.
[0061]
number
[0062] The precipitation behavior of such fine precipitates 20 has a large effect on the mechanical properties and hydrogen delayed fracture properties of the formed part after hot stamping. Hereinafter, the difference in the improvement effect on the mechanical properties and hydrogen delayed fracture properties of the formed part after hot stamping depending on the precipitation behavior of the fine precipitates 20 will be described with reference to Figs. 2A to 3B.
[0063] 2A and 2B are diagrams illustrating a part of a state in which fine precipitates are dispersed according to an embodiment of the present invention.
[0064] Specifically, FIG. 2A illustrates a case where the size and distribution of fine precipitates 20 dispersed within the steel plate 10 are relatively non-uniform, and FIG. 2B illustrates a case where the size and distribution of fine precipitates 20 dispersed within the steel plate 10 are relatively uniform.
[0065] Referring to FIG. 2A, the fine precipitates 20 are distributed unevenly within the steel sheet 10, but in a biased manner. As a result, a region in which a relatively large number of the fine precipitates 20 are aggregated may exist in a certain region within the steel sheet 10. Furthermore, a relatively large number of defects (e.g., dislocations, etc.) may be aggregated in the region in which a relatively large number of the fine precipitates 20 are aggregated. Furthermore, when the size of the fine precipitates 20 is not uniform as in FIG. 2A, a relatively large number of defects (e.g., dislocations, etc.) may be aggregated in the relatively large fine precipitates 20. In other words, the defects may also be distributed unevenly within the steel sheet 10, but in a biased manner.
[0066] In this way, when a relatively large number of defects (e.g., dislocations) are concentrated in a specific region, the region acts as a fracture notch, inducing non-uniform stress distribution and stress concentration, resulting in a problem of deteriorating mechanical properties such as strength and bendability.
[0067] 2B, fine precipitates 20 of relatively uniform size are uniformly dispersed within the steel sheet 10. As a result, defects (e.g., dislocations, etc.) are relatively uniformly distributed within the steel sheet 10, which has the effect of minimizing or preventing the occurrence of regions that act as notches.
[0068] In one embodiment, the number of fine precipitates 20 dispersed within the steel sheet 10 per unit area can be controlled to satisfy a preset range. 2 The number of fine precipitates 20 per 100 μm is 25,000 or more and 30,000 or less. That is, the number of fine precipitates 20 per 100 μm is 25,000 or more and 30,000 or less. 2 More than 30,000 pieces / 100μm 2 It can be formed as follows:
[0069] In addition, among the fine precipitates 20 dispersed inside the steel sheet 10, the unit area (100 μm) of the fine precipitates 20 having a diameter of 0.01 μm or less is 2 The number of fine precipitates 20 per 100 μm is 23,000 or more and 29,000 or less. That is, the number of fine precipitates 20 per 100 μm is 23,000 or more and 29,000 or less in the steel sheet 10. 2 More than 29,000 pieces / 100μm 2 It can be formed as follows:
[0070] In addition, among the fine precipitates 20 dispersed inside the steel sheet 10, the unit area (100 μm) of the fine precipitates 20 having a diameter of 0.005 μm or less is 2 The number of fine precipitates 20 per 100 μm is 15,200 or more and 29,000 or less. That is, the number of fine precipitates 20 per 100 μm is 15,200 or more and 29,000 or less in the steel sheet 10. 2 More than 29,000 pieces / 100μm 2 It can be formed as follows:
[0071] If the number of fine precipitates 20 per unit area satisfies the above-mentioned range, the tensile strength (e.g., 1,680 MPa or more) required after hot stamping can be ensured, and the formability or bendability can be improved. For example, if the number of fine precipitates 20 is 25,000 / 100 μm 2 The number of fine precipitates 20 with a diameter of 0.01 μm or less is 23,000 / 100 μm 2 The number of fine precipitates 20 with a diameter of 0.005 μm or less is 15,200 / 100 μm 2 If the number of fine precipitates 20 is less than 30,000 pieces / 100 μm, the strength may be reduced. 2 The number of fine precipitates 20 exceeding 29,000 / 100μm or having a diameter of 0.01μm or less is 29,000 / 100μm 2 The number of fine precipitates 20 exceeding 29,000 / 100μm or having a diameter of 0.005μm or less is 29,000 / 100μm 2 If it exceeds this value, formability or bendability may be reduced.
[0072] In the following, unit area (100 μm 2 The coefficient of variation of the number average, which indicates the uniformity of the distribution of the number of fine precipitates by size (diameter) per total fine precipitates, may be referred to as the second coefficient of variation (C2). The second coefficient of variation (C2) may be defined as the standard deviation of the number average divided by the number average. In one embodiment, the second coefficient of variation (C2) may be about 0.8 or less. If the second coefficient of variation (C2) exceeds about 0.8, the bendability may be deteriorated. Specifically, if the distribution of the number of fine precipitates is non-uniform, the density reduction of the block boundary through the refinement of the prior austenite grain size (PAGS) is reduced in the region where the fine precipitates are distributed in small amounts, and therefore, a problem may occur in which it is difficult to secure a sufficient slip band. Therefore, if the second coefficient of variation (C2) exceeds about 0.8, the formability and bendability may be deteriorated. The precipitation behavior relating to the number distribution via the second coefficient of variation (C2) will be described in further detail with reference to the comparative examples and examples described later.
[0073] In one embodiment, the average distance between adjacent fine precipitates 20 can be controlled to satisfy a preset range. Here, "average distance" refers to the mean free path of the fine precipitates 20, and the details of the method for measuring it will be described later.
[0074] Specifically, the average distance between the fine precipitates 20 is about 0.15 μm or more and about 0.4 μm or less. If the average distance between the fine precipitates 20 is less than about 0.15 μm, the formability or bendability may be reduced, while if it exceeds about 0.4 μm, the strength may be reduced.
[0075] The diameter of the fine precipitates 20 can have a large effect on the improvement of delayed hydrogen fracture resistance. Hereinafter, the difference in the improvement effect of delayed hydrogen fracture resistance depending on the diameter of the fine precipitates 20 will be described with reference to Figs. 3A and 3B.
[0076] 3A and 3B are diagrams that diagrammatically show a part of the state in which hydrogen is trapped in the fine precipitates 20. FIG.
[0077] Specifically, FIG. 3A illustrates the state in which hydrogen is trapped in fine precipitates 20 having a relatively large diameter, and FIG. 3B illustrates the state in which hydrogen is trapped in fine precipitates 20 having a relatively small diameter.
[0078] As shown in FIG. 3A, when the diameter of the fine precipitates 20 is relatively large, the number of hydrogen atoms trapped in one fine precipitate 20 may increase. That is, the hydrogen atoms flowing into the steel sheet 10 may not be uniformly dispersed, and the probability that multiple hydrogen atoms are trapped in one hydrogen trapping site may increase. Multiple hydrogen atoms trapped in one hydrogen trapping site may combine with each other to form hydrogen molecules (H2). The formed hydrogen molecules may increase the probability of internal pressure generation, and as a result, may deteriorate the hydrogen delayed fracture properties of the hot stamped product.
[0079] In contrast, when the diameter of the fine precipitates 20 is relatively small as shown in Fig. 3B, the probability of multiple hydrogen atoms being trapped in one fine precipitate 10 may be reduced. That is, hydrogen atoms flowing into the steel sheet 10 may be relatively uniformly dispersed by being trapped in different hydrogen trapping sites. As a result, hydrogen atoms are unable to bond with each other, reducing the probability of internal pressure generation due to hydrogen molecules, and improving the hydrogen delayed fracture properties of products processed by hot stamping.
[0080] In the hot stamping steel sheet 1 according to an embodiment of the present invention, the average diameter of the fine precipitates 20 dispersed within the steel sheet 10 may be controlled to satisfy a preset range in order to improve hydrogen delayed fracture properties. Specifically, the average diameter of the fine precipitates 20 dispersed within the steel sheet 10 may be about 0.006 μm or less. Furthermore, about 90% or more of the fine precipitates 20 dispersed within the steel sheet 10 may have a diameter of about 0.01 μm or less. Furthermore, about 60% or more of the fine precipitates 20 dispersed within the steel sheet 10 may have a diameter of about 0.005 μm or less.
[0081] In the following, unit area (100 μm 2) may be referred to as the first coefficient of variation (C1). The first coefficient of variation (C1) may be defined as the standard deviation of the average diameter of all fine precipitates divided by the average diameter. In one embodiment, the first coefficient of variation (C1) may satisfy about 0.7 or less. If the first coefficient of variation (C1) exceeds about 0.7, the tensile strength and hydrogen delayed fracture properties may be reduced. Specifically, if the size (diameter) distribution of the fine precipitates is non-uniform, the non-uniform diameter distribution may act as an obstruction factor for dislocation movement, and the strength may be reduced. That is, if an external impact is applied to the steel sheet after hot stamping, a portion where fine precipitates having a large size (diameter) are densely packed may act as a fracture notch due to dislocation accumulation. In addition, the amount of hydrogen trapped in the fine precipitates is non-uniform, and hydrogen delayed fracture properties may be reduced due to a local increase in hydrogen partial pressure caused by hydrogen-hydrogen bonding. The precipitation behavior relating to the diameter distribution via the first coefficient of variation (C1) will be described in further detail through comparative examples and examples described later.
[0082] The refinement of the fine precipitates 20 may improve the bending properties of the formed part after hot stamping. In one embodiment, the refined fine precipitates 20 act as an impediment to grain growth and may refine the primary austenite grain size (PAGS). As the primary austenite grain size (PAGS) is refined, the martensite packet size and the martensite lath phase size may be reduced. This reduces the block boundary interval within the packet, and the block density may be increased. Such block boundaries may act as slip bands during deformation of the martensite structure due to an external impact, and the refinement of the fine precipitates 20 may ensure more slip bands, which may contribute to improving the bending properties.
[0083] FIG. 4 is a flow chart that illustrates a schematic diagram of a method for manufacturing a blank for hot stamping according to an embodiment of the present invention.
[0084] As shown in FIG. 4, a method for manufacturing a material for hot stamping according to an embodiment of the present invention includes a reheating step (S100), a hot rolling step (S200), a cooling / coiling step (S300), a cold rolling step (S400), an annealing heat treatment step (S500), and a plating step (S600).
[0085] For reference, in FIG. 4, steps S100 to S600 are illustrated as independent steps, but some of steps S100 to S600 may be performed in a single process, and some may be omitted if necessary.
[0086] First, a semi-finished slab to be used in the process of forming the hot stamping material 1 is prepared. The slab contains 0.28-0.50% by weight of carbon (C), 0.15-0.70% by weight of silicon (Si), 0.5-2.0% by weight of manganese (Mn), more than 0 and 0.05% by weight or less of phosphorus (P), more than 0 and 0.01% by weight or less of sulfur (S), 0.1-0.5% by weight of chromium (Cr), 0.001-0.005% by weight of boron (B), more than 0 and 0.1% by weight or less of additives, and the balance is iron (Fe) and other unavoidable impurities. In this case, the additive contains at least one of titanium (Ti), niobium (Nb), and vanadium (V). For example, the titanium (Ti), niobium (Nb) and / or vanadium (V) content may be from about 0.010% to about 0.050% by weight.
[0087] The reheating step (S100) is a step of reheating the slab for hot rolling. In the reheating step (S100), the slab obtained through the continuous casting process is reheated within a predetermined temperature range, so that the components segregated during casting can be redissolved.
[0088] The slab reheating temperature (SRT) can be controlled within a preset temperature range to refine austenite and maximize the precipitation hardening effect. The SRT range is within a temperature range (about 1,000°C or higher) where additives (Ti, Nb and / or V) are fully dissolved based on the equilibrium precipitation amount of fine precipitates 20 during slab reheating. If the SRT does not reach the full solution temperature range of additives (Ti, Nb and / or V), the driving force required for microstructure control during hot rolling is not fully reflected, and the desired effect of ensuring excellent mechanical properties through precipitation amount control cannot be obtained.
[0089] In one embodiment, the slab reheat temperature (SRT) may be controlled to about 1,200°C to about 1,250°C. If the slab reheat temperature (SRT) is less than about 1,200°C, the components segregated during casting may not be sufficiently redissolved, and the homogenization effect of the alloy elements may not be large, and the dissolution effect of titanium (Ti) may not be large. The higher the slab reheat temperature (SRT), the more favorable it is for homogenization. However, if the SRT exceeds about 1,250°C, the austenite grain size increases, making it difficult to ensure strength, and the manufacturing cost of the steel plate may increase due to the excessive heating process.
[0090] The hot rolling step (S200) is a step of manufacturing a steel sheet by hot rolling the slab reheated in the step S100 in a predetermined finishing delivery temperature (FDT) range. In one embodiment, the finishing delivery temperature (FDT) range can be controlled to about 840°C to about 920°C. If the finishing delivery temperature (FDT) is less than 840°C, a duplex structure due to abnormal region rolling occurs, making it difficult to ensure the workability of the steel sheet, and there is a problem that the workability is reduced due to the unevenness of the microstructure. In addition, a problem of sheet threadability during hot rolling may occur due to a sudden phase change. On the other hand, if the finishing delivery temperature (FDT) exceeds 920°C, austenite grains may become coarse. In addition, there is a risk that TiC precipitates become coarse and the performance of the final part may be reduced.
[0091] In addition, in the reheating step (S100) and the hot rolling step (S200), some of the fine precipitates 20 may be precipitated at the grain boundaries where the energy is unstable. At this time, the fine precipitates 20 precipitated at the grain boundaries act as an element that hinders the crystal grain growth of austenite, and can provide the effect of improving strength through austenite refinement. In addition, the fine precipitates 20 precipitated in the S100 and S200 steps are at a level of about 0.007 wt% based on the equilibrium precipitation amount, but are not limited thereto.
[0092] The cooling / coiling step (S300) is a step in which the steel sheet hot-rolled in the step S200 is cooled in a predetermined coiling temperature (CT) range and coiled to form fine precipitates 20 in the steel sheet. That is, in the step S300, nitrides or carbides of additives (Ti, Nb and / or V) contained in the slab are formed to form fine precipitates 20. The coiling may be carried out in the ferrite region so that the equilibrium precipitation amount of the fine precipitates 20 reaches a maximum value. In this way, when the structure is transformed into ferrite after the crystal grain recrystallization is completed, the particle size of the fine precipitates 20 may be uniformly precipitated not only at the grain boundaries but also within the grain boundaries.
[0093] In one embodiment, the coiling temperature (CT) is about 700°C to about 780°C. The coiling temperature (CT) may affect the redistribution of carbon (C). If the coiling temperature (CT) is less than about 700°C, the low temperature phase fraction increases due to supercooling, increasing the strength, and there is a concern that the rolling load during cold rolling will increase, and there is a problem that the ductility will be rapidly reduced. On the other hand, if the coiling temperature exceeds about 780°C, there is a problem that abnormal crystal grain growth or excessive crystal grain growth will cause deterioration of formability and strength.
[0094] In this way, according to this embodiment, the precipitation behavior of the fine precipitates 20 can be controlled by controlling the coiling temperature (CT) range. Experimental examples relating to changes in the properties of the material for hot stamping 1 depending on the coiling temperature (CT) range will be described later with reference to Figs. 5, 6A, and 6B.
[0095] The cold rolling step (S400) is a step of uncoiling the steel sheet coiled in the step S300, pickling the steel sheet, and then cold rolling the steel sheet. The pickling is performed to remove scale from the coiled steel sheet, i.e., the hot-rolled coil manufactured through the above-mentioned hot rolling process. In one embodiment, the reduction ratio during cold rolling may be controlled to 30% to 70%, but is not limited thereto.
[0096] The annealing heat treatment step (S500) is a step of annealing the steel sheet cold rolled in the S400 step at a temperature of about 700° C. or more. In one embodiment, the annealing heat treatment includes the steps of heating the cold rolled sheet material and cooling the heated cold rolled sheet material at a predetermined cooling rate.
[0097] The plating step (S600) is a step of forming a plating layer on the annealed heat-treated steel sheet. In one embodiment, in the plating step (S600), an Al-Si plating layer may be formed on the steel sheet that has been annealed in the S500 step.
[0098] Specifically, the plating step (S600) includes a step of immersing the steel sheet in a plating bath having a temperature of about 650° C. to about 700° C. to form a hot-dip plating layer on the surface of the steel sheet, and a cooling step of cooling the steel sheet on which the hot-dip plating layer has been formed to form a plating layer. At this time, the plating bath contains additive elements such as Si, Fe, Al, Mn, Cr, Mg, Ti, Zn, Sb, Sn, Cu, Ni, Co, In, Bi, etc., but is not limited thereto.
[0099] By performing a hot stamping process on the blank 1 for hot stamping manufactured through steps S100 to S600, the conditions related to the precipitation behavior of the fine precipitates 20 described above are satisfied, and thus a hot stamped part having the required strength and bendability can be manufactured. As an example, the blank 1 for hot stamping manufactured to satisfy the above content conditions and process conditions may have a tensile strength of 1,680 MPa or more, a bendability of 50° or more, and an activated hydrogen content of 0.8 wppm or less after hot stamping.
[0100] Hereinafter, the present invention will be described in more detail through examples and comparative examples. However, the following examples and comparative examples are provided to more specifically explain the present invention, and the scope of the present invention is not limited by the following examples and comparative examples. The following examples and comparative examples may be appropriately modified or altered by those skilled in the art within the scope of the present invention. FIG. 5 is a graph comparing the tensile strength and bending stress according to the winding temperature of the examples and comparative examples of the present invention, and FIG. 6A and FIG. 6B are images illustrating the results of a 4-point bending test according to the winding temperature of the examples and comparative examples.
[0101] The Example (CT700) and Comparative Example (CT800) are specimens manufactured by hot stamping the hot stamping blank 1 manufactured by carrying out the above-mentioned steps S100 to S600 for a slab having the composition as shown in Table 1 below. Here, the Example (CT700) and Comparative Example (CT800) are specimens manufactured by applying the same content conditions and process conditions in the manufacturing process of the hot stamping blank 1, but applying only the coiling temperature (CT) as a variable. Specifically, the Example (CT700) and Comparative Example (CT800) are specimens produced by hot stamping a slab having the composition shown in Table 1 under the following conditions: slab reheating temperature (SRT): 1,230°C, finish rolling temperature (FDT): 900°C, hot rolling reduction: 95%, annealing heat treatment temperature: 780°C, and galvanizing immersion temperature: 660°C, after heating at 950°C for 270 seconds, by hot stamping.
[0102] [Table 1]
[0103] Specifically, the embodiment (CT700) is a specimen manufactured by hot stamping the hot stamping material 1 manufactured by applying a coiling temperature (CT) of 700°C, and the comparative example (CT800) is a specimen manufactured by hot stamping the hot stamping material 1 manufactured by applying a coiling temperature (CT) of 800°C.
[0104] Here, description will be made with reference to Fig. 5. Fig. 5 is a graph showing the tensile strength and bending stress of the example (CT700) and the comparative example (CT800).
[0105] Referring to FIG. 5, in terms of tensile strength, the tensile strength of the Example (CT700) is stronger than that of the Comparative Example (CT800), and it can be seen that the bending stress, which affects the impact properties, is also improved in the Example (CT700) compared to the Comparative Example (CT800).
[0106] This is because, as can be seen from Table 2 below, the amount of fine precipitates 20 in the example (CT700) was increased compared to the comparative example (CT800), and the hydrogen trapping ability was improved accordingly.
[0107] Table 2 below shows the equilibrium precipitation amount, the measured amount of activated hydrogen, and the results of the bent-beam stress corrosion test for the embodiment (CT700) and the comparative example (CT800). Here, the equilibrium precipitation amount means the maximum number of precipitates that can be precipitated when a thermodynamic equilibrium state is reached, and the greater the equilibrium precipitation amount, the greater the number of precipitates that are precipitated. In addition, the amount of activated hydrogen means the amount of hydrogen that has flowed into the steel sheet 10, excluding the hydrogen trapped in the fine precipitates 20.
[0108] The amount of activated hydrogen can be measured using thermal desorption spectroscopy. Specifically, a specimen is heated at a preset heating rate, and the amount of hydrogen released from the specimen below a specific temperature is measured. Here, the hydrogen released from the specimen below a specific temperature can be understood as activated hydrogen that cannot be trapped among hydrogen that has flowed into the specimen and affects hydrogen delayed fracture.
[0109] [Table 2]
[0110] Table 2 shows the results of a four-point bending test for each sample having a different equilibrium amount of fine precipitates, and the amount of activated hydrogen measured using the thermal degassing analysis method.
[0111] The four-point bending test is a test method in which a specimen is manufactured by simulating a state where the specimen is exposed to a corrosive environment, and stress below the elastic limit is applied at a specific point to check whether or not stress corrosion cracking occurs. Here, the stress corrosion cracking refers to cracking that occurs when corrosion and sustained tensile stress act simultaneously.
[0112] Specifically, the four-point bending test results in Table 2 are the results of applying a stress of 1,000 MPa to each sample in air for 100 hours to check whether or not fracture occurred. The amount of activated hydrogen was measured using the above-mentioned thermal degassing analysis method, and was the value obtained by measuring the amount of hydrogen released from the specimen at 350°C or lower while heating each sample from room temperature to 500°C at a heating rate of 20°C / min.
[0113] Referring to Table 2, in the case of the equilibrium precipitation amount of the fine precipitates 20, the equilibrium precipitation amount of the example (CT700) was measured to be 0.040 wt%, and the equilibrium precipitation amount of the comparative example (CT800) was measured to be 0.029 wt%. In other words, it can be confirmed that the example (CT700) can provide more hydrogen trapping sites by forming more fine precipitates 20 compared to the comparative example (CT800).
[0114] In addition, in the four-point bending test, the Example (CT700) did not break, while the Comparative Example (CT800) broke. In addition, in the case of the amount of activated hydrogen, the amount of activated hydrogen of the Example (CT700) was measured to be about 0.453 wppm, while the amount of activated hydrogen of the Comparative Example (CT800) was measured to be about 0.550 wppm. In relation to this, it can be confirmed that the Example (CT700), which has a relatively lower amount of activated hydrogen, did not break, while the Comparative Example (CT800), which has a relatively higher amount of activated hydrogen, broke. This can be understood as meaning that the hydrogen delayed fracture properties of the Example (CT700) are improved compared to the Comparative Example (CT800).
[0115] That is, the amount of fine precipitates 20 in the example (CT700) was increased compared to the comparative example (CT800), and the amount of activated hydrogen was reduced. This means that the amount of hydrogen trapped inside the example (CT700) was increased compared to the comparative example (CT800), and as a result, it can be understood that the hydrogen delayed fracture properties were improved.
[0116] 6A and 6B are images illustrating the results of a four-point bending test performed on the example (CT700) and the comparative example (CT800), respectively. Specifically, Fig. 6A shows the results of a four-point bending test performed on the example (CT700), and Fig. 6B corresponds to the results of a four-point bending test performed on the comparative example (CT800) under the same conditions as the example (CT700).
[0117] As shown in FIG. 6A and FIG. 6B, in the four-point bending test, the specimen of the embodiment (CT700) was not broken, whereas the specimen of the comparative example (CT800) was broken.
[0118] In the case of the embodiment (CT700) of FIG. 6A, the specimen is manufactured by hot stamping the hot stamping blank 1 manufactured by applying a coiling temperature (CT) of 700° C., and fine precipitates 20 having a diameter of 0.01 μm or less are formed in a unit area (100 μm 2 The number of fine precipitates 20 per one steel sheet is 23,000 or more and 29,000 or less, and the average distance between the fine precipitates 20 is 0.15 μm or more and 0.4 μm or less. Therefore, it can be confirmed that the example (CT700) efficiently disperses and traps hydrogen that has flowed into the steel sheet 10, thereby improving the hydrogen delayed fracture properties, and improving the tensile strength and bending properties.
[0119] 6B, the comparative example (CT800) is a specimen manufactured by hot stamping the hot stamping material 1 manufactured by applying a coiling temperature (CT) of 800°C, and the amount of precipitation of the fine precipitates 20 is insufficient, the diameter of the fine precipitates 20 is coarsened, and the probability of occurrence of pressure resistance due to hydrogen bonding increases. Therefore, it can be confirmed that the comparative example (CT800) is unable to efficiently disperse and trap hydrogen that has flowed into the steel sheet 10, and thus the tensile strength, bending properties, and hydrogen delayed fracture properties are deteriorated.
[0120] That is, even if the hot stamping material 1 is composed of the same components, the strength, bendability, and hydrogen delayed fracture properties of the hot stamping material 1 after the hot stamping process differ depending on the coiling temperature (CT). This is because the precipitation behavior of the fine precipitates 20 differs depending on the coiling temperature (CT). Therefore, by applying the content conditions and process conditions according to the above-mentioned embodiment of the present invention, it is possible to ensure high strength and improve bendability and hydrogen delayed fracture properties.
[0121] Tables 3 to 6 below show numerical values of tensile strength, bendability, and hydrogen delayed fracture properties for a plurality of specimens, which are dependent on the difference in precipitation behavior of the fine precipitates 20. Specifically, Tables 3 to 6 show measured values of precipitation behavior (number of fine precipitates, average distance between fine precipitates, diameter of fine precipitates, etc.) and measured values of properties (tensile strength, bendability, and amount of activated hydrogen) possessed after hot stamping for a plurality of specimens.
[0122] The test pieces were each heated to 950°C and cooled to 300°C or less at a cooling rate of 30°C / s or more, after which the tensile strength, bendability and amount of activated hydrogen were measured. The tensile strength and amount of activated hydrogen were measured based on the above-mentioned four-point bending test and thermal degassing analysis method, and the bendability was measured by measuring the V-bending angle according to VDA238-100, the standard of the Association of the German Automotive Industry (VDA: Verband Der Automobilindustrie).
[0123] The precipitation behavior of fine precipitates (number of fine precipitates, average distance between fine precipitates, diameter of fine precipitates, etc.) was measured through the above-mentioned TEM image analysis. The precipitation behavior of fine precipitates was measured in an arbitrary region having an area of 0.5 μm x 0.5 μm, and the precipitation behavior was measured in a unit area (100 μm 2 ) was converted and measured based on the standard.
[0124] [Table 3]
[0125] [Table 4]
[0126] [Table 5]
[0127] [Table 6]
[0128] Tables 3 to 6 show the measured values of the precipitation behavior of fine precipitates (number of fine precipitates, average distance between fine precipitates, diameter of fine precipitates, etc.) for specimens A to V, and the measured values of the properties (tensile strength, bendability, and amount of activated hydrogen) after hot stamping.
[0129] Specimens A to K are specimens manufactured by hot stamping the hot stamping materials manufactured through steps S100 to S600 by applying the above-mentioned process conditions to the slab satisfying the content conditions shown in Table 3. Specimens A to K are specimens manufactured by heating the hot stamping materials manufactured under the conditions of slab reheating temperature (SRT): 1,230°C, finish rolling temperature (FDT): 900°C, hot rolling reduction: 95%, coiling temperature (CT): 780°C, annealing heat treatment temperature: 780°C, and galvanizing immersion temperature: 660°C for 270 seconds at 950°C and then hot stamping. In other words, specimens A to K are specimens that satisfy the above-mentioned precipitation behavior conditions of fine precipitates.
[0130] Specifically, in specimens A to K, fine precipitates were present in the steel sheet at 25,000 particles / 100 μm. 2 More than 30,000 pieces / 100μm 2 The average diameter of all fine precipitates is 0.006 μm or less, and the average distance between all fine precipitates is 0.15 μm or more and 0.4 μm or less. In addition, 90% or more of the fine precipitates formed in the steel sheet have a diameter of 0.01 μm or less, and the number of fine precipitates having a diameter of 0.01 μm or less is 23,000 / 100 μm. 2 More than 29,000 pieces / 100μm 2 The following is satisfied. In addition, 60% or more of the fine precipitates formed in the steel sheet have a diameter of 0.005 μm or less, and the number of fine precipitates having a diameter of 0.005 μm or less is 15,200 / 100 μm. 2 More than 29,000 pieces / 100μm 2 Satisfy the following.
[0131] It can be confirmed that the specimens A to K, which satisfy the precipitation behavior conditions of the present invention, have improved tensile strength, bendability, and hydrogen delayed fracture properties. Specifically, the specimens A to K have a tensile strength of 1,680 MPa or more after hot stamping, a bendability of 40° or more after hot stamping, and an activated hydrogen content of 0.5 wppm or less after hot stamping.
[0132] Specimens L to V are specimens manufactured by hot stamping the hot stamping material manufactured through steps S100 to S600 by applying the above-mentioned process conditions to the slab satisfying the content conditions shown in Table 5. Specimens L to V are specimens manufactured by hot stamping the hot stamping material manufactured under the conditions of slab reheating temperature (SRT): 1,230°C, finish rolling temperature (FDT): 900°C, hot rolling reduction: 95%, coiling temperature (CT): 790°C, annealing heat treatment temperature: 780°C, and galvanizing immersion temperature: 660°C, by heating the hot stamping material at 950°C for 270 seconds and then hot stamping it. In other words, specimens L to V are specimens that cannot satisfy at least a part of the precipitation behavior conditions of the fine precipitates described above, and it can be confirmed that the tensile strength, bendability, and / or hydrogen delayed fracture properties are inferior to specimens A to K.
[0133] In the case of specimen L, the number of fine precipitates with a diameter of 0.01 μm or less is 22,998. This does not reach the lower limit of the condition for the number of fine precipitates with a diameter of 0.01 μm or less. Therefore, it can be confirmed that the tensile strength of specimen L is only 1,671 MPa, which is relatively low.
[0134] In the case of specimen M, the total number of fine precipitates was 24,999, and the number of fine precipitates with a diameter of 0.01 μm or less was 22,874. This does not reach the lower limit of the total number of fine precipitates and the lower limit of the number of fine precipitates with a diameter of 0.01 μm or less. Therefore, it can be confirmed that the tensile strength of specimen M is only 1,664 MPa, which is relatively low.
[0135] In the case of specimen N, the number of fine precipitates with a diameter of 0.01 μm or less is 29,005, which exceeds the upper limit of the condition for the number of fine precipitates with a diameter of 0.01 μm or less. This confirms that the bendability of specimen N is relatively low at only 37°.
[0136] In the case of specimen O, the total number of fine precipitates is 30,009, which exceeds the upper limit of the total number of fine precipitates. Therefore, it can be confirmed that the bendability of specimen O is only 35°, which is relatively low.
[0137] In the case of specimen P, the overall average diameter of fine precipitates is 0.0071 μm, which exceeds the upper limit of the overall average diameter of fine precipitates. Therefore, the amount of activated hydrogen in specimen P is measured to be relatively high at 0.505 wppm, and it can be confirmed that the hydrogen delayed fracture properties are relatively deteriorated.
[0138] This does not reach the lower limit of the ratio of fine precipitates with a diameter of 0.005 μm or less. As a result, the amount of activated hydrogen in specimen Q was measured as 0.514 wppm, which is relatively high, and it can be confirmed that the hydrogen delayed fracture properties were relatively deteriorated.
[0139] In the case of specimen R, the ratio of fine precipitates with a diameter of 0.005 μm or less is 59.9%, which does not reach the lower limit of the ratio condition for fine precipitates with a diameter of 0.005 μm or less. Therefore, the amount of activated hydrogen in specimen R was measured as 0.502 wppm, which is relatively high, and it can be confirmed that the hydrogen delayed fracture properties were relatively deteriorated.
[0140] In the case of specimen S, the ratio of fine precipitates with a diameter of 0.005 μm or less is 59.7%, which does not reach the lower limit of the ratio of fine precipitates with a diameter of 0.005 μm or less. Therefore, the amount of activated hydrogen in specimen S was measured as 0.504 wppm, which is relatively high, and it can be confirmed that the hydrogen delayed fracture properties were relatively deteriorated.
[0141] In the case of specimen T, the average distance between all fine precipitates is 0.14 μm, which does not reach the lower limit of the average distance between all fine precipitates. Therefore, it can be confirmed that the bendability of specimen T is only 38°, which is relatively low.
[0142] In the case of specimen U, the overall average distance of fine precipitates is 0.41 μm, which exceeds the upper limit of the overall average distance of fine precipitates. Therefore, it can be confirmed that the tensile strength of specimen U is only 1,678 MPa, which is relatively low.
[0143] In the case of specimen V, the number of fine precipitates with a diameter of 0.005 μm or less is 15,112, which does not reach the lower limit of the condition for the number of fine precipitates with a diameter of 0.005 μm or less. This confirms that the tensile strength is only 1,671 MPa, which is relatively low.
[0144] The following describes the difference in the improvement effect of the tensile strength and hydrogen delayed fracture properties of the formed parts after hot stamping depending on the precipitation behavior of the fine precipitates 20 with reference to Table 7. The precipitation behavior of the fine precipitates below was measured through the above-mentioned TEM image analysis. The precipitation behavior of the fine precipitates was measured for 10 random regions having an area of 0.5 μm x 0.5 μm, and the precipitation behavior was calculated based on the unit area (100 μm 2 ), and hereinafter, "average" refers to the average of the precipitation behavior values relating to an arbitrary region. The total number of precipitates in the arbitrary region is calculated, and their average value is referred to as the "total precipitate number average." Similarly, the average distance between fine precipitates is calculated via the mean free path in the arbitrary region, and their average value is referred to as the "average distance between precipitates." The numbers of fine precipitates with a diameter of 10 nm or less and fine precipitates with a diameter of 5 nm or less in the arbitrary region are respectively calculated per unit area (100 μm 2 ) and calculate the average value, and then the ratio to the above-mentioned "total precipitate number average" is referred to as the "average ratio of 10 nm or less" and the "average ratio of 5 nm or less."
[0145] The average diameter between all fine precipitates in the above-mentioned arbitrary region is called "total precipitate diameter average", and the standard deviation of these values is called "standard deviation of diameter average". The diameter average variation coefficient, i.e., the first variation coefficient (C1) is defined as the value obtained by dividing the standard deviation of the diameter average by the diameter average. In the present invention, the first variation coefficient (C1) is also 0.8 or less.
[0146] [Table 7]
[0147] Table 7 is a numerical representation of the tensile strength and hydrogen delayed fracture properties according to the precipitation behavior of fine precipitates for a number of specimens. Specifically, Table 7 lists, as the precipitation behavior of fine precipitates for a number of specimens (X1 to X12), the overall number average of fine precipitates, the average distance between fine precipitates, the average ratio of fine precipitates having a specific diameter or less, the overall diameter average of fine precipitates, the standard deviation of the diameter average, and measurements for the first coefficient of variation (C1), as well as the resulting properties after hot stamping, namely, the tensile strength and the amount of activated hydrogen. In particular, the tensile strength and hydrogen delayed fracture properties according to the first coefficient of variation (C1), which is the coefficient of variation of the diameter average, will be described.
[0148] Specimens X1 to X12 are specimens produced by hot stamping the hot stamping material produced through steps S100 to S600 under the above-mentioned process conditions for a slab containing carbon (C): 0.28 to 0.50 wt%, silicon (Si): 0.15 to 0.70 wt%, manganese (Mn): 0.5 to 2.0 wt%, phosphorus (P): more than 0 to 0.05 wt%, sulfur (S): more than 0 to 0.01 wt%, chromium (Cr): 0.1 to 0.5 wt%, boron (B): 0.001 to 0.005 wt%, the sum of one or more of titanium (Ti), niobium (Nb), and vanadium (V): more than 0 to 0.1 wt%, and the balance iron (Fe) and other unavoidable impurities. Here, specimens X1 to X12 are specimens manufactured by hot stamping a hot stamping material manufactured under the conditions of slab reheating temperature (SRT): 1,230°C, finish rolling temperature (FDT): 900°C, hot rolling reduction: 95%, coiling temperature (CT): 780°C, annealing heat treatment temperature: 780°C, and galvanizing immersion temperature: 660°C, which is heated at 950°C for 270 seconds and then hot stamped. Specimens X1 to X12 can satisfy not only the precipitation behavior related to the first coefficient of variation (C1) but also the precipitation behavior related to the second coefficient of variation (C2) described above. That is, specimens X1 to X12 are specimens that satisfy the precipitation behavior conditions of fine precipitates described above.
[0149] Specifically, the total number of fine precipitates in specimens X1 to X12 was 25,000 to 30,000 / μm 2 the average distance between adjacent fine precipitates is 0.15 μm or more and 0.40 μm or less, the ratio of fine precipitates having a diameter of 0.01 μm or less is 90% or more, the ratio of fine precipitates having a diameter of 0.005 μm or less is 60% or more, and the average diameter of all fine precipitates is 0.006 μm or less.
[0150] However, specimens X1 to X8 satisfy the condition that the first coefficient of variation is 0.7 or less, while specimens X9 to X12 have a first coefficient of variation exceeding 0.7 and therefore cannot satisfy the precipitation behavior condition according to the first coefficient of variation of the present invention. It can be confirmed that specimens X1 to X8, which have a first coefficient of variation of 0.7 or less, are superior in tensile strength and hydrogen delayed fracture properties to specimens X9 to X12, which have a first coefficient of variation exceeding 0.7. Specifically, after hot stamping, specimens X1 to X8 have a tensile strength of 1,700 MPa or more and an activated hydrogen amount of 0.4 wppm or less. In comparison, specimens X9 to X12 have a tensile strength of 1,680 MPa to 1,700 MPa (less than 1,700 MPa) and an activated hydrogen amount of 0.4 wppm to 0.5 wppm after hot stamping. In comparison, specimens X1 to X8 have superior tensile strength and hydrogen delayed fracture properties compared to specimens X9 to X12.
[0151] In particular, specimens X1 to X4 have an average total number of precipitates of 25,000 or more and 27,500 or less, of which the average ratio of fine precipitates with a diameter of 10 nm or less is 90% to 92%, and the average ratio of fine precipitates with a diameter of 5 nm or less is 60% to 63%, and since the total number of precipitates and the ratio of fine precipitates with a diameter of 10 nm or less or 5 nm or less are low, it is also a condition under which it is very difficult to ensure tensile strength and hydrogen delayed fracture properties after hot stamping. Nevertheless, specimens X1 to X4 satisfy the precipitation behavior condition of the present invention that the first coefficient of variation is 0.7 or less, and therefore have relatively high tensile strength and hydrogen delayed fracture properties compared to specimens X9 to X12.
[0152] In addition, specimen X12 has a relatively high average number of precipitates, 29,424, and the ratios of fine precipitates with diameters of 10 nm or less and 5 nm or less are also high, 97.1% and 91.4%, respectively, which are relatively favorable conditions for securing tensile strength and hydrogen delayed fracture properties. Nevertheless, specimen X12 does not satisfy the precipitation behavior condition of the present invention, that is, the first coefficient of variation is 0.7 or less, and therefore has relatively low tensile strength and hydrogen delayed fracture properties compared to specimens X1 to X8.
[0153] The following describes the difference in the effect of improving the bendability of a molded part after hot stamping, depending on the precipitation behavior of the fine precipitates 20, with reference to Table 8. The precipitation behavior of the fine precipitates below was measured through the above-mentioned TEM image analysis. The precipitation behavior of the fine precipitates was measured for 10 random areas having an area of 0.5 μm x 0.5 μm, and the precipitation behavior was calculated based on the unit area (100 μm 2 ) as a standard, and hereinafter, "average" refers to the average of the precipitation behavior values relating to an arbitrary region. After measuring the total number of precipitates, the number of fine precipitates with a diameter of 10 nm or less, and the number of fine precipitates with a diameter of 5 nm or less in the arbitrary region, the unit area (100 μm 2 ) as a standard, and the respective average values are referred to as the "total precipitate number average," the "10 nm or less precipitate number average," and the "5 nm or less precipitate number average," and the respective standard deviations are measured. The average distance between fine precipitates is calculated via the mean free path in the arbitrary region, and the average value thereof is referred to as the "precipitate distance average."
[0154] The number variation coefficient, i.e., the second variation coefficient (C2), is defined as the standard deviation of the number average divided by the number average. In the present invention, the second variation coefficient (C2) is also 0.8 or less. The second variation coefficient (C2) includes the 2-1st variation coefficient (C21), which is the number variation coefficient of fine precipitates having a diameter of 10 nm or less, and the 2-2nd variation coefficient (C22), which is the number variation coefficient of fine precipitates having a diameter of 5 nm or less.
[0155] The 2-1st coefficient of variation (C21) is defined as the standard deviation of the number average of fine precipitates having a diameter of 0.01 μm or less among all fine precipitates, divided by the number average among fine precipitates having a diameter of 0.01 μm or less, and the 2-1st coefficient of variation (C21) is also 0.8 or less. Hereinafter, the 2-1st coefficient of variation (C21) may be referred to as the "first number coefficient of variation". The 2-2nd coefficient of variation (C22) is defined as the standard deviation of the number average of fine precipitates having a diameter of 0.005 μm or less among all fine precipitates, divided by the number average among fine precipitates having a diameter of 0.005 μm or less, and the 2-2nd coefficient of variation (C22) is also 0.8 or less. Hereinafter, the 2-2nd coefficient of variation (C22) may be referred to as the "second number coefficient of variation".
[0156] [Table 8]
[0157] Table 8 is a numerical value of the bending angle according to the precipitation behavior of fine precipitates for a number of specimens. Specifically, Table 8 lists, as the precipitation behavior of fine precipitates for a number of specimens (Y1 to Y14), the number average of all fine precipitates, fine precipitates with a diameter of 10 nm or less, and fine precipitates with a diameter of 5 nm or less, the standard deviation of the number average, the measured value for the second coefficient of variation (C2) which is the coefficient of variation of the number of fine precipitates, and the measured value for the bending angle as the properties after hot stamping based on the measured values. In particular, the bendability based on the second coefficient of variation (C2) which is the coefficient of variation of the number average will be described.
[0158] Specimens Y1 to Y14 are specimens produced by hot stamping the hot stamping material produced through steps S100 to S600 under the above-mentioned process conditions for a slab containing 0.28-0.50 wt% carbon (C), 0.15-0.70 wt% silicon (Si), 0.5-2.0 wt% manganese (Mn), 0.05 wt% or less phosphorus (P), 0.05 wt% or more sulfur (S), 0.1-0.5 wt% chromium (Cr), 0.001-0.005 wt% boron (B), and the sum of one or more of titanium (Ti), niobium (Nb), and vanadium (V) as additives: 0.1 wt% or less, and the balance being iron (Fe) and other unavoidable impurities. Here, specimens Y1 to Y14 are specimens produced by hot stamping a hot stamping material produced under the conditions of slab reheating temperature (SRT): 1,230°C, finish rolling temperature (FDT): 900°C, hot rolling reduction: 95%, coiling temperature (CT): 780°C, annealing heat treatment temperature: 780°C, and galvanizing immersion temperature: 660°C, which was heated at 950°C for 270 seconds and then hot stamped. Specimens Y1 to Y14 can satisfy not only the precipitation behavior related to the second coefficient of variation (C2) described below, but also the precipitation behavior related to the first coefficient of variation (C1) described above. That is, specimens Y1 to Y14 are specimens that satisfy the precipitation behavior conditions of fine precipitates described above.
[0159] Specifically, the total number of fine precipitates in specimens Y1 to Y14 was 25,000 to 30,000 / μm 2 The average distance between adjacent fine precipitates is 0.15 μm or more and 0.40 μm or less, and the number of fine precipitates with a diameter of 10 nm or less is 23,000 to 29,000 / μm. 2 The number of fine precipitates with a diameter of 5 nm or less is 15,200 to 29,000 per μm. 2 Although not shown in Table 8, in each of specimens Y1 to Y14, the ratio of fine precipitates having a diameter of 0.01 μm or less is 90% or more, the ratio of fine precipitates having a diameter of 0.005 μm or less is 60% or more, and the average diameter of all fine precipitates satisfies 0.006 μm or less.
[0160] However, specimens Y1 to Y8 satisfy the condition that the second coefficient of variation is 0.8 or less, while specimens Y9 to Y14 have a second coefficient of variation exceeding 0.8, and thus cannot satisfy the precipitation behavior condition according to the second coefficient of variation of the present invention. It can be confirmed that specimens Y1 to Y8, which have a second coefficient of variation of 0.8 or less, have better bending properties than specimens Y9 to Y14, which have a first coefficient of variation exceeding 0.8. Specifically, specimens Y9 to Y14 have a bending angle (°) of 40° to 50° after hot stamping, whereas specimens Y9 to Y14 have a bending angle of 50° to less than 60° after hot stamping, and specimens Y1 to Y8 have better bending properties than specimens Y9 to Y14.
[0161] In the case of specimen Y9, the second coefficient of variation (C2), the second-1 coefficient of variation (C21), and the second-2 coefficient of variation (C22) were 0.82, 0.81, and 0.81, respectively, which exceeded the upper limit (0.8) of the number-based coefficient of variation (C2, C21, C22) condition. This confirmed that the bendability of specimen Y9 was only 44°, which is relatively low.
[0162] In the case of specimens Y10 to Y12, the second coefficient of variation (C2) is 0.81 to 0.85, which exceeds the upper limit of the second coefficient of variation (C2) condition. As a result, it can be confirmed that the bending angle of specimens Y10 to Y12 is only relatively low, 42° to 45°. In the case of specimen Y13, the second-first coefficient of variation (C21) is 0.82, which exceeds the upper limit of the second-first coefficient of variation (C21) condition. As a result, it can be confirmed that the bending angle of specimen Y13 is only relatively low, 43°. In the case of specimen Y14, the second-second coefficient of variation (C22) is 0.82, which exceeds the upper limit of the second-second coefficient of variation (C22) condition. As a result, it can be confirmed that the bending angle of specimen Y14 is only relatively low, 41°.
[0163] In particular, specimens Y5 to Y8 are 2The average number of precipitates per sample is 28,000 or more and 30,000 or less, and among them, the number of fine precipitates with a diameter of 10 nm or less and fine precipitates with a diameter of 5 nm or less are also relatively high, which makes it difficult to ensure bendability. Nevertheless, Samples Y5 to Y8 satisfy the precipitation behavior condition of the present invention, that is, the second coefficient of variation is 0.8 or less, and therefore have relatively high bendability compared to Samples Y9 to Y14.
[0164] In addition, specimens Y9 to Y14 have a large number of total precipitates, fine precipitates having a diameter of 10 nm or less, and 5 nm or less, which is relatively favorable for ensuring bendability. Nevertheless, specimens Y9 to Y14 do not satisfy the precipitation behavior condition of the present invention, that is, the second coefficient of variation is 0.8 or less, and therefore have relatively poor bendability compared to specimens Y1 to Y8.
[0165] As a result, it was confirmed that the hot stamping material manufactured by the manufacturing method of the hot stamping material applying the content conditions and process conditions of the present invention satisfies the precipitation behavior conditions of the fine precipitates after hot stamping, and the hot stamping product satisfying the precipitation behavior conditions of the fine precipitates has improved tensile strength, bendability, and hydrogen delayed fracture properties. In particular, it was confirmed that the hot stamping material according to the embodiment of the present invention satisfies the average diameter variation coefficient and / or number variation coefficient among the precipitation behavior conditions, and the number and size (diameter) of the fine precipitates are uniformly distributed, so that the tensile strength, bendability, and hydrogen delayed fracture properties of the molded part after hot stamping are further improved.
[0166] The present invention has been described with reference to the embodiments shown in the drawings, but they are merely illustrative, and those skilled in the art will understand that various modifications and equivalent embodiments are possible therefrom. Therefore, the true technical scope of the present invention is defined by the technical ideas of the claims.
Claims
1. a steel plate containing carbon (C): 0.28 to 0.50 weight %, silicon (Si): 0.15 to 0.70 weight %, manganese (Mn): 0.5 to 2.0 weight %, phosphorus (P): more than 0 and not more than 0.05 weight %, sulfur (S): more than 0 and not more than 0.01 weight %, chromium (Cr): 0.1 to 0.5 weight %, boron (B): 0.001 to 0.005 weight %, additives: more than 0 and not more than 0.1 weight %, the balance being iron (Fe), and other unavoidable impurities; and fine precipitates distributed within the steel sheet. The additive includes at least one of titanium (Ti), niobium (Nb), and vanadium (V), The fine precipitates contain at least one nitride or carbide of titanium (Ti), niobium (Nb), and vanadium (V), and trap hydrogen; A material for hot stamping, wherein a coefficient of variation of the average diameter, which is a value obtained by dividing the standard deviation of the average diameter of the fine precipitates by the average diameter of the fine precipitates, is 0.7 or less.
2. 2. The material for hot stamping according to claim 1, which exhibits, after hot stamping, a tensile strength of 1,680 MPa or more, a bending angle of 40° or more, and an activated hydrogen content of 0.5 wppm or less.
3. 2. The material for hot stamping according to claim 1, wherein the fine precipitates have an average diameter of 0.006 μm or less.
4. The material for hot stamping according to claim 3, wherein 90% or more of the fine precipitates have a diameter of 0.01 μm or less.
5. 5. The blank for hot stamping according to claim 4, wherein 60% or more of the fine precipitates have a diameter of 0.005 μm or less.
6. The unit area (100 μm 2 2. The material for hot stamping according to claim 1, wherein the number of pieces per one piece is 25,000 or more and 30,000 or less.
7. The unit area (100 μm) of fine precipitates having a diameter of 0.01 μm or less 2 The material for hot stamping according to claim 6, wherein the number of pieces per one piece is 23,000 or more and 29,000 or less.
8. The unit area (100 μm) of fine precipitates having a diameter of 0.005 μm or less 2 8. The material for hot stamping according to claim 7, wherein the number of pieces per one piece is 15,200 or more and 29,000 or less.
9. 2. The material for hot stamping according to claim 1, wherein a coefficient of variation in number, which is a value obtained by dividing the standard deviation of the number average of the fine precipitates by the number average of the fine precipitates, is 0.8 or less.
10. a steel plate containing carbon (C): 0.28 to 0.50 weight %, silicon (Si): 0.15 to 0.70 weight %, manganese (Mn): 0.5 to 2.0 weight %, phosphorus (P): more than 0 and not more than 0.05 weight %, sulfur (S): more than 0 and not more than 0.01 weight %, chromium (Cr): 0.1 to 0.5 weight %, boron (B): 0.001 to 0.005 weight %, additives: more than 0 and not more than 0.1 weight %, the balance being iron (Fe), and other unavoidable impurities; Fine precipitates distributed within the steel sheet; Including, The additive includes at least one of titanium (Ti), niobium (Nb), and vanadium (V), The fine precipitates contain at least one nitride or carbide of titanium (Ti), niobium (Nb), and vanadium (V), and trap hydrogen; A material for hot stamping, wherein a coefficient of variation in number, which is a value obtained by dividing the standard deviation of the number average of the fine precipitates by the number average of the fine precipitates, is 0.8 or less.
11. 11. The material for hot stamping according to claim 10, which exhibits a tensile strength of 1,680 MPa or more, a bending angle of 40° or more, and an activated hydrogen content of 0.5 wppm or less after hot stamping.
12. The material for hot stamping according to claim 10, wherein a first number variation coefficient, which is a value obtained by dividing the standard deviation of the number average of fine precipitates having a diameter of 0.01 μm or less among the fine precipitates, by the number average of the fine precipitates having a diameter of 0.01 μm or less, is 0.8 or less.
13. The hot stamping material according to claim 12, wherein a second number variation coefficient, which is a value obtained by dividing the standard deviation of the number average of fine precipitates having a diameter of 0.005 μm or less among the fine precipitates, by the number average of the fine precipitates having a diameter of 0.005 μm or less, is 0.8 or less.
14. The unit area (100 μm 2 The material for hot stamping according to claim 10, wherein the number of pieces per one piece is 25,000 or more and 30,000 or less.
15. The unit area (100 μm) of fine precipitates having a diameter of 0.01 μm or less 2 The material for hot stamping according to claim 14, wherein the number of pieces per one piece is 23,000 or more and 29,000 or less.
16. The unit area (100 μm) of fine precipitates having a diameter of 0.005 μm or less 2 The material for hot stamping according to claim 15, wherein the number of pieces per one piece is 15,200 or more and 29,000 or less.
17. The material for hot stamping according to claim 10, wherein the fine precipitates have an average diameter of 0.006 μm or less.
18. 18. The blank for hot stamping according to claim 17, wherein 90% or more of the fine precipitates have a diameter of 0.01 μm or less.
19. 19. The blank for hot stamping according to claim 18, wherein 60% or more of the fine precipitates have a diameter of 0.005 μm or less.
Citation Information
Patent Citations
Steel sheet for hot press formed products having excellent bendability and ultra-high strength, hot press formed products using the same, and manufacturing methods thereof
JP2017508069A
Method for producing a steel sheet for press hardening, and component obtained by said method
JP2017525849A
Silver powder for conductive paste with improved viscosity stability and method for producing the same
KR1020210119733A
Hot stamping component and method of manufacturing the same
US20210187583A1
Steel sheet for hot stamping members and method for producing same
WO2012147863A1
